2013
DOI: 10.3390/su5114523
|View full text |Cite
|
Sign up to set email alerts
|

The Modern Phosphorus Sustainability Movement: A Profiling Experiment

Abstract: Abstract:Since the -peak phosphorus‖ concept emerged in 2007, concerns about the future availability of phosphate rock have funneled into a growing number of actions, often in the form of new and innovative platforms focusing on phosphorus sustainability. This trend seems to continue on different levels and in different formats, which makes the landscape of activities increasingly blurred and complex. This article considers the emerging phase of the modern phosphorus sustainability movement. It provides a firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The biogeochemistry of soil phosphorus (P) is complex and is governed by numerous factors, including soil type, soil management and use, vegetation type, and local environmental factors. Understanding the soil's capacity to adsorb P is critical in determining the best nutrient management plan for enhancing P fertilizers' agronomic value and mitigating related environmental risks (Olsen & Watanabe, 1957; Sims & Pierzynski, 2005; Ulrich & Schnug, 2013). The increased use of P fertilizer following the Green Revolution (Cordell et al., 2009) and expansion of the dairy industry (Achat et al., 2014; Barnett, 1994; Cordeiro et al., 2019; Kinley et al., 2007; Liu et al., 2018) resulted in P applications above the amounts needed by crops.…”
Section: Introductionmentioning
confidence: 99%
“…The biogeochemistry of soil phosphorus (P) is complex and is governed by numerous factors, including soil type, soil management and use, vegetation type, and local environmental factors. Understanding the soil's capacity to adsorb P is critical in determining the best nutrient management plan for enhancing P fertilizers' agronomic value and mitigating related environmental risks (Olsen & Watanabe, 1957; Sims & Pierzynski, 2005; Ulrich & Schnug, 2013). The increased use of P fertilizer following the Green Revolution (Cordell et al., 2009) and expansion of the dairy industry (Achat et al., 2014; Barnett, 1994; Cordeiro et al., 2019; Kinley et al., 2007; Liu et al., 2018) resulted in P applications above the amounts needed by crops.…”
Section: Introductionmentioning
confidence: 99%
“…As shown by Ulrich and Schnug (2013), since 2008 multistakeholder platforms have been formed and researchers have intensified their effort in tackling the challenges related to P. Material flow analysis (MFA) has played a key role in assessing flows and stocks and identifying hotspots of poor management and recycling potential, as manifested by two recent reviews of P MFAs carried out at different scales throughout the world (Cordell et al 2012;Chowdhury et al 2014). Until recently, these studies have primarily focused on static 1-year budgets (balanced models of material flows and stocks obtained through MFA methodology), and the review carried out by Chowdhury and colleagues (2014) identified the paucity of multiyear analyses as a major knowledge gap.…”
Section: One-year and Historical Phosphorus Materials Flow Analysismentioning
confidence: 84%
“…As shown by Ulrich and Schnug (), since 2008 multistakeholder platforms have been formed and researchers have intensified their effort in tackling the challenges related to P. Material flow analysis (MFA) has played a key role in assessing flows and stocks and identifying hotspots of poor management and recycling potential, as manifested by two recent reviews of P MFAs carried out at different scales throughout the world (Cordell et al. ; Chowdhury et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, this short-term crisis triggered substantial and sudden interest in the longerterm issue of global phosphorus scarcity. A flurry of science media reports (e.g., 48), scientific articles (e.g., 5,49), and new multistakeholder platforms (e.g., the Global Phosphorus Research Initiative, the Dutch Nutrient Platform, the US Sustainable Phosphorus Initiative, and Global TraPs) emerged directly addressing the issue and raising awareness at the international level (50,51). Having been ignored in the past, the scarcity of phosphorus began to appear in authoritative reports by key international documents on global food security (23,52,53).…”
Section: Dimensions Of Phosphorus Scarcitymentioning
confidence: 99%